On the ldentity of Murdannia juncoides (Wight) R. S. Rao & Kammathy (Commelinaceae) - Nampy, Santhosh; Paul, Joby (Rheedea, 2008)
The little known, rare and endemic Murdannia juncoides (Wight) Rolla & Kammathy is often considered conspecific with M.semrteres(Dalz.) Sant. Critical study of the types and live specimens have shown that both the species are distinct. Detailed description andillustration of M. juncoides are provided. Distinguishing characters separating M. juncoides from the allied M. semiteres are given.